Factors affecting service delivery at the University of Limpopo with a special reference to administrative and secretariat challenges - Choeu, Mmokela Meisie (My University, 2019)
For South African higher education institutions to compete globally, they must be able to provide quality service to their clients and stakeholders. The increasing competition puts pressure on institutions to strive to be the best. The importance of quality service delivery cannot be over-emphasised. Students are there to receive education that will enable them to meet the market requirements which will, in turn, improve the economy of the country. Therefore, all staff members of the university, including the administrative staff of Faculty of Science and Agriculture, cannot be excluded from this. Recent challenges and the University of Limpopo have also exerted a lot of pressure on the administrative staff and secretaries to deliver quality services to its clients. The administrative staff from the Faculty of Science and Agriculture are not excluded from the above challenges, hence the study on factors affecting service delivery at the University of Limpopo focuses on them. The performance of the administrative staff in the Faculty of Science and Agriculture depends on the factors that influence them to deliver quality services in the area of the study. Service delivery at the University of Limpopo was fraught with challenges such as lack of clarity on policies and alternative strategies, inadequate resources, lack of managerial skills, monitoring and evaluation. The study also seeks to investigate the factors that hinder effective service delivery by the administration at the university. The data were obtained by means of questionnaires and semi-structured interviews. These were then used to gain a deeper understanding of the challenges that were encountered by the respondents in the area of the study. The findings of the study confirm that there are negative factors that are associated with the implementation of service delivery in the area of the study. Lack of staff development and relevant training to the administrative staff were regarded as the main challenges that hinder quality service delivery in the Faculty of Science and Agriculture. In conclusion, the study also suggests some strategies and recommendations that can enhance effective service delivery in the area of the study.
Thesis (MPA.) -- University of Limpopo, 2019
Keywords: South Africa; Institution; Students; Service delivery; University of Limpopo; Administration; Administrative; Service delivery; Universities and colleges -- Services for